The Notorious Harmful Algal Blooms-Forming Dinoflagellate Prorocentrum donghaiense Produces Sexual Resting Cysts, Which Widely Distribute Along the Coastal Marine Sediment of China - Hu, Zhangxi; Liu, Yuyang; Deng, Yunyan; Tang, Ying Zhong (Frontiers in Marine Science, 2022)
The armored dinoflagellate Prorocentrum donghaiense distributes globally and has been forming large scale and dense ecosystem disruptive algal blooms (EDABs) in the East China Sea (ECS) almost every year since the 1990s and often in other coastal waters of the world. It has long been a mystery, however, about how these blooms were seeded or where the initiating population came from. In this work, we provide a more feasible and universal seeding mechanism, formation of resting cysts. Using light microscopy, we confirmed sexual reproduction according to the observations of mating cells in pairs, planozygotes having two similar flagella, darkened and thick-walled resting cysts with smooth surface, and germination processes of resting cyst. Using morpho-molecular detection, we confirmed P. donghaiense resting cyst in the field, including the positive detections of polymerase chain reaction (PCR) using species-specific primers and then the fluorescence in situ hybridization (FISH) using species-specific probes, and further confirmation via single-cell sequencing for the individual FISH-detected cysts. Furthermore, the distribution and abundance of P. donghaiense cysts along the coast of China Seas were mapped using an approach combining real-time PCR (qPCR) and FISH, with the qPCR quantification taking into account the doubled copy number of LSU rRNA gene in resting cysts. Resting cysts of this species were found to widely distribute in the Yellow Sea (YS), ECS, and South China Sea (SCS), with a relatively low abundance at most sampling sites, but to be absent in the eight samples from the Bohai Sea (BS). Resting cyst production confirmed with evidences from both laboratory cultures and field sediments and the extensive distribution of cysts in the China Seas, as the first case in planktonic species of Prorocentrum, not only filled up a knowledge gap about the life history of P. donghaiense but also provided a possible mechanistic facility to seed the annual blooms in the ECS and the global distribution of the species.